Knowledge, attitudes and practices regarding milk powder usage among mothers of 1-5 year old children in Pitakotte MOH area - Gankanda, W. I.; Gunathilake, I. A. G. M. P.; Weliange, S.; Wickramasinghe, V. P. (Sri Lanka college of pediatricians, 2011)
Introduction: Early childhood nutrition plays an important role in growth and development of children. However, due to false beliefs of parents, undue prominence has been given to milk in the child’s diet. Objective: To assess the knowledge, attitudes, practices and factors related to milk powder usage among mothers of 1-5 year old children. Method: A cross sectional study was carried out among 187 mothers of 1-5 year old children in five randomly selected weighing centres in Pitakotte MOH area using an interviewer administered questionnaire. Scores were given to knowledge, attitudes and practice. Results: The mean age of the children was 32 (SD 16.3) months. Mothers’ knowledge on milk/milk powder and their usage was good in 20% and level of attitudes was good in 55%. Parents received information regarding milk powder from doctors (42.4%) and TV advertisements (36.5%). The commonest factor mothers considered when selecting a milk powder was the brand name (69.7%). Mean age of initiating cow’s milk was 13.5 (SD 9.2) months. Forty seven percent selected a single brand to start feeding their children. At the time of conducting the survey, 47% were using one particular brand of full cream. While 52.8% gave concentrated milk, 33.7% gave diluted milk. One hundred and one (62%) used a cup while 44 (27%) used a bottle to give milk. Sixty (36.8%) mothers were giving the correct volume of milk, while 95 (58.3%) gave more than recommended. There was a statistically significant association between social class and level of practice (χ 2 =5.19;p<0.05;df=1). Practice was not significantly associated with mother’s level of attitudes, knowledge, age, education, parity or the sex of the child.Conclusions: Knowledge and practice regarding milk and milk powder usage among mothers is poor. Mothers of lower social classes have a good level of practice. ________________________________________
Keywords: Knowledge; attitudes; practices; milk powder usage; mothers